Unusual Spinal Epidural Lipomatosis and Lumbosacral Instability - David Ruiz Picazo; José Ramírez Villaescusa (Case Reports in Orthopedics)
Introduction. Epidural lipomatosis is most frequently observed in patients on chronic steroid treatment. Only a few idiopathic epidural lipomatosis cases have been described. Material and Methods. 64-year-old male patient presented with low back pain and left leg pain. Later, the patient experienced neurogenic claudication and radicular pain in the left leg without urinary dysfunction. Plain radiography and magnetic resonance imaging demonstrated an abnormal fat tissue overgrowth in the epidural space with compression of the dural sac, degenerative disc disease at L4-L5 level, and instability at L5-S1. Endocrinopathic diseases and chronic steroid therapy were excluded. If conservative treatment failed, surgical treatment can be indicated. Results. After surgery, there was a gradual improvement in symptoms and signs, and six months later the patient returned to daily activities and was neurologically normal. Conclusion. In the absence of common causes of neurogenic claudication, epidural lipomatosis should be considered. The standard test for the diagnosis of epidural lipomatosis is magnetic resonance (MR). At first, conservative treatment must be considered; weight loss and the suspension of prior corticosteroid therapy are indicated. In the presence of neurological impairment, the operative treatment of wide surgical decompression must be performed soon after diagnosis.